Correlation of Bite Force Interpretation in Maximal Intercuspal Position among Patient, Clinician, and T-Scan III System - Ruttitivapanich, Nitikarn; Tansalarak, Ratchawan; Palasuk, Jadesada; Pumklin, Jittima (European Journal of Dentistry, 2019)
Objective The main purpose of this article was to determine the correlation of bite force in maximal intercuspal position (MIP) among patient’s perceptions, clinician subjective interpretation, and T-Scan III system.Materials and Methods Forty-three dental students at Naresuan University (Phitsanulok, Thailand) participated in the study. Subjects were positioned by Frankfurt horizontal plane paralleled to the horizontal plane and asked to bilaterally clenched in MIP. Patient’s perception was evaluated by asking which side of the jaw had heavier bite force (right, left, or equally on both sides). Then, the clinician subjective interpretation was assessed using traditional occlusal indicators. Furthermore, patient’s bite force was analyzed using T-Scan III.Statistical Analysis Cohen’s weighted kappa test was used to evaluate the correlation of bite force.Results The best correlation between patient’s perception and T-Scan III was at the ± 7.5% cutoff range with 15 subject agreements. While the best correlation between clinician subjective interpretation and T-Scan III was at ± 5.0% cutoff range with 23 subject agreements. Cohen’s weighted kappa indicated slight agreement between T-Scan III and patient’s perception and fair agreement between T-Scan III and clinician.Conclusions Clinician subjective interpretation is more clinically reliable than patient’s perception when T-Scan III is used as a gold standard.
Keywords: T-Scan; bite force; occlusal indicators